Oxaliplatin-induced loss of phosphorylated heavy neurofilament subunit neuronal immunoreactivity in rat DRG tissue - Connor Bronwen; Ip Virginia; Jong Nancy N; Liu Johnson J; Subramaniam Joshuan; Jamieson Stephen MF; McKeage Mark J (SAGE Publishing, 2009)
Abstract Background Oxaliplatin and related chemotherapeutic drugs cause painful chronic peripheral neuropathies in cancer patients. We investigated changes in neuronal size profiles and neurofilament immunoreactivity in L5 dorsal root ganglion (DRG) tissue of adult female Wistar rats after multiple-dose treatment with oxaliplatin, cisplatin, carboplatin or paclitaxel. Results After treatment with oxaliplatin, phosphorylated neurofilament heavy subunit (pNF-H) immunoreactivity was reduced in neuronal cell bodies, but unchanged in nerve fibres, of the L5 DRG. Morphometric analysis confirmed significant changes in the number (-75%; P < 0.0002) and size (-45%; P < 0.0001) of pNF-H-immunoreactive neurons after oxaliplatin treatment. pNF-H-immunoreactive neurons had overlapping size profiles and co-localisation with neurons displaying cell body immunoreactivity for parvalbumin, non-phospho-specific neurofilament medium subunit (NF-M) and non-phospho-specific neurofilament heavy subunit (NF-H), in control DRG. However, there were no significant changes in the numbers of neurons with immunoreactivity for parvalbumin (4.6%, P = 0.82), NF-M (-1%, P = 0.96) or NF-H (0%; P = 0.93) after oxaliplatin treatment, although the sizes of parvalbumin (-29%, P = 0.047), NF-M (-11%, P = 0.038) and NF-H (-28%; P = 0.0033) immunoreactive neurons were reduced. In an independent comparison of different chemotherapeutic agents, the number of pNF-H-immunoreactive neurons was significantly altered by oxaliplatin (-77.2%; P < 0.0001) and cisplatin (-35.2%; P = 0.03) but not by carboplatin or paclitaxel, and their mean cell body area was significantly changed by oxaliplatin (-31.1%; P = 0.008) but not by cisplatin, carboplatin or paclitaxel. Conclusion This study has demonstrated a specific pattern of loss of pNF-H immunoreactivity in rat DRG tissue that corresponds with the relative neurotoxicity of oxaliplatin, cisplatin and carboplatin. Loss of pNF-H may be mechanistically linked to oxaliplatin-induced neuronal atrophy, and serves as a readily measureable endpoint of its neurotoxicity in the rat model.